Intrathecal Bupivacaine with Fentanyl Versus Bupivacaine Alone for Caesarean Section Under Spinal Anesthesia - Zanyar Noori Osman (Advanced Medical Journal)
Background and objectives: Postoperative pain might start due to the decrement effect of anesthetic drugs. Complications are reduced and recovery hastens with post-surgical pain control. The aim of this study is to evaluate the effect of spinal anesthesia by combining drugs (Bupivacaine and Fentanyl) versus Bupivacaine alone, to manage postoperative pain.